Pengaruh Perencanaan Sumber Daya Manusia dan Pelatihan Terhadap Peningkatan Kapabilitas APIP pada Inspektorat Kabupaten Mesuji Provinsi Lampung - Esti Suci Yanti; Hendri Dunan; Riswan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Doctor retention is a critical issue for regional hospitals in ensuring sustainable healthcare services. This study This study aims to analyze the effect of human resource planning and training on the improvement of the capability of the Government Internal Supervisory Apparatus (Aparat Pengawasan Intern Pemerintah/APIP) at the Inspectorate of Mesuji Regency, Lampung Province. The research problem focuses on the need to further strengthen APIP capability in supporting the effectiveness of internal supervision within local government. The research approach is based on a conceptual framework integrating Human Capital Theory, the Resource-Based View, and Organizational Capability Theory, which emphasize the importance of human resource management and training as strategic factors in enhancing organizational capability. The research employed a quantitative approach with a survey design, and the data were analyzed using multiple linear regression supported by classical assumption tests, t-tests, F-tests, and the coefficient of determination. The results indicate that human resource planning and training have a positive and significant effect on APIP capability, both partially and simultaneously. The conclusion of this study confirms that improving APIP capability requires integrated human resource planning accompanied by well-structured, relevant, and sustainable training programs.